Service Enhancement Opportunity Of Design And Build Project In Trans Papua Project - Fitriana Prahastiwi Pramono; Akbar Adhi Utama (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2026)
This study examines how design-review inefficiencies in a design-and-build infrastructure project can be reduced through process reengineering and digital collaboration, using the Trans Papua Project as an empirical case. A mixed-methods case study was employed by combining quantitative project-control analysis and qualitative process diagnosis. Schedule Performance Index and Schedule Variance were calculated from verified monthly progress reports, while semi-structured interviews with project personnel were analysed using qualitative content analysis. The study then integrated stakeholder analysis, Process Chain Network, value co-creation, DART-PDCA, Building Information Modelling within a Common Data Environment, and Analytical Hierarchy Process to evaluate alternative process-redesign scenarios. The findings show that schedule risk was driven not only by construction productivity constraints but also by technical data misalignment, sequential review routines, and fragmented stakeholder interfaces. Among three PCN alternatives, Alternative 1 was prioritised because it balanced formal design-consultant involvement, contractor-led cost and constructability evaluation, parallel submission of design alternatives, process efficiency, and stakeholder acceptance. Its short-term implementation improved SPI from 1.11 in June 2025 to 1.17 in September 2025. This study contributes to design-and-build infrastructure governance by demonstrating how PCN and BIM-CDE can transform sequential design review into a more collaborative, traceable, and parallel decision-making process in Indonesian public-private infrastructure delivery.